Lessons Learned from the Preimplementation Phase of an Oral Health Care Project. (July 2023) - Murray, J.; Hunter, S.C.; Splawinski, Z.; Conroy, T.
Implementation research aims to improve uptake of evidence-based interventions into health care practice and policy, but conducting such research can be complex. This brief report discusses the intentions of the research team versus the reality faced when conducting the preimplementation phase of a project aiming to improve adherence to best-practice oral health care in a hospital geriatric unit. Using our project as an example, our aim is to provide researchers with an insight into potential hurdles they may also face and strategies that could be employed to overcome these. During the preimplementation stage, it is important to take sufficient time to ensure that the local site is ready and motivated for the proposed change and committed to the shared goal. Explicit delineation of roles of facilitators is needed. Contextual circumstances will always change, and additional support or resources might be required to navigate them. A flexible mind-set is required as goals and strategies may need to be renegotiated along the way. The success and effectiveness of implementation projects are often built from the time and relationship building invested in the preimplementation phase. Knowledge Transfer Statement: This commentary highlights that effective implementation of best-practice oral health care in acute geriatric units is built on the time and relationship building invested in the preimplementation phase.